Characteristics of Bobotoh Football Supporters in Providing Militant Support to PERSIB - Defrianto, Budi; Rahayu, Tandiyo; Hidayah, Taufiq (Journal of Physical Education and Sports, 2021)
This research is motivated by the diverse characteristics that exist among Bobotoh Supporters in their efforts to support Persib, such that the character possessed by each individual generates a variety of perspectives among fellow Bobotoh. This is a qualitative study using a phenomenological approach, which refers to a method that explains the similarity of meaning that exists between concepts or phenomena in a group or individual. The data for this study came from Bobotoh Supporters, who were represented by two districts, Viking Galuh Ciamis and Viking Cirebon, which included the Supporter’s chief and members residing in West Java.According to the findings of this study, the characteristics of Bobotoh supporters who support Persib are generally favorable, although they vary by match. The association between Bobotoh Supporters’ characteristics and the match will be consistent if Bobotoh has excellent character while watching the match. The ideal Bobotoh Supporter possesses the following characteristics: Bobotoh who is prudent in responding to match results, vigilant in purchasing match tickets, honest in supporting Persib, and never causes Persib to suffer losses. The research concludes that the characteristics of Bobotoh Supporters in West Java already exhibit positive characteristics as supporters; however, under certain circumstances, even when Bobotoh exhibits positive characteristics, the emotionality of each individual Bobotoh Supporter remains difficult to control, particularly during Super Bigmatch matches involving rivals. Therefore, there are still a large number of characters in Bobotoh Supporters who support Persib, particularly during the Super Bigmatch match.